2008
DOI: 10.1121/1.2821972
|View full text |Cite
|
Sign up to set email alerts
|

Noise in the operating rooms of Greek hospitals

Abstract: This study is an evaluation of the problem of noise pollution in operating rooms. The high sound pressure level of noise in the operating theatre has a negative impact on communication between operating room personnel. The research took place at nine Greek public hospitals with more than 400 beds. The objective evaluation consisted of sound pressure level measurements in terms of L(eq), as well as peak sound pressure levels in recordings during 43 surgeries in order to identify sources of noise. The subjective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 26 publications
(24 reference statements)
1
60
0
2
Order By: Relevance
“…In several studies, 9,13,16,17,20 the highest noise levels were found in the ORs in which orthopedic surgery was performed. In three studies, 11,12,20 the noisiest period proved to be during anesthesia …”
Section: Noise Levels In the Ormentioning
confidence: 96%
See 1 more Smart Citation
“…In several studies, 9,13,16,17,20 the highest noise levels were found in the ORs in which orthopedic surgery was performed. In three studies, 11,12,20 the noisiest period proved to be during anesthesia …”
Section: Noise Levels In the Ormentioning
confidence: 96%
“…In six studies, 8,11,12,[19][20][21] noise sources in the OR were identified. The primary noise sources identified were:…”
Section: Noise Sourcesmentioning
confidence: 99%
“…21 No que diz respeito ao ambiente cirúrgico, um estudo realizado em salas operatórias de nove hospitais públicos na Grécia encontrou um valor médio de 71,9dB durante as cirurgias reiterando a afirmação de que os equipamentos e as pessoas do próprio ambiente são as principais fontes de ruídos encontrada. 22 Esta pesquisa está em consonância com os resultados encontrados na literatura nacional e internacional, demonstrando um elevado e preocupante nível de ruído ambiental hospitalar, acima das normas regulamentadoras.…”
Section: Discussionunclassified
“…Also, operating rooms in the hospitals are quite noisy places. The high sound pressure level of noise in the operating theatre has a negative impact on communication between operating room personnel (17). Noise pollution makes errors more probable and is one of the risk factors for provider burnout and negative outcomes for patients (18).…”
Section: Discussionmentioning
confidence: 99%